KORESPONDENSI MANUSIA DAN KOSMOS DALAM KOSMOLOGI SUFISME IBNU 'ARABI DAN ACHMAD ASRORI AL-ISHAQI - Yaqin, Ainul (UIN Sunan Kalijaga Yogyakarta, 2021)
This research aims to determine the ihwal of correspondence between humans and cosmos according to the Sufism cosmological’s thingking of Ibn ‘Arabi and al-Ishaqi, which of course these two ideas will be compared. This ihwal correspondence caused a polemic because it was closely related to divine thing. In the Sufism cosmology, humans and the cosmos were placed in a position that aimed at reflecting God’s self-manifestation. To determine the ihwal correspondence, this research use library research method. Meanwhile to achieve the result of data analysis as expected, the study uses inductive and comparative method also analysis from hermeneutic theory of Hans-Georg Gadamer. The result of this research determine that Ibn ‘Arabi and al-Ishaqi approve this two entity that become one each other to keep and preserve the actualization of God’s self-manifestation. But, according al-Ishaqi, this correspondence places the universe as part of human, because human is macrocosm and cosmos is microcosm. This thought different with Ibn ‘Arabi which positions human as part of the universe with the cosmic structure that said human is microcosm and cosmos is macrocosm. Despite different this specification, human and cosmos have to complement each other to achieve His-determination like interaction between subjects each other.